Evolution, culture, and Care for Betta splendens - Craig A. Watson; Matt DiMaggio; Jeffery E. Hill; Quenton M. Tuckett; Roy P. Yanong (EDIS)
The commercial betta, or Siamese fighting fish (Betta splendens), is one of a group of fishes that live in fresh water in Africa and southern Asia. Today’s commercial bettas are selected for bright colors as well as elaborate fins because the ornamental hobby is the main market for this species. This 5-page fact sheet written by Craig Watson, Matthew DiMaggio, Jeffrey Hill, Quenton Tuckett, and Roy Yanong and published by School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences explains how to grow and care for these beautiful and fascinating fishes. http://edis.ifas.ufl.edu/fa212